Impacts of socio-economic statuses on youth crime in Sri Lanka - Jayasuriya, S. D.; Ramanayake, S. S. (International Conference on Child Protection 2025, University of Kelaniya, Sri Lanka., 2025)
Background: Sri Lanka is a developing country, and the contribution of its youth plays a crucial role in the nation's progress. However, increased youth involvement in crime has a negative impact on the country in various ways. An increasing number of youth crimes significantly affects the country and the safety of the people, and this has become a huge issue related to the socioeconomic status of young people engaging in criminal activities. Therefore, the primary objective of this study was to identify the impacts of socioeconomic statuses on youth crime in Sri Lanka. Method: A mixed-method approach was used for this analysis, based on primary data. The rationale for applying mixed methods is the complicated and multifaceted nature of youth crimes, which cannot be obtained only through figures or statistics. As a sample, 100 convicted male young prisoners between the ages of 18 to 29 were selected through simple random sampling, and the sample size was defined by the Yamane method. Data was collected using survey questionnaire methods. Descriptive analysis, chi-square analysis, and binary logistic regression analysis were used to analyze data. Results: The key findings indicated significant association (0.05>P>0.000) between youth criminal behavior and socioeconomic statuses, including the variables of residence, family income, school education level, peer influence, and substance (drugs or alcohol) influence. Furthermore, a descriptive analysis also revealed that 42% of young prisoners committed their first offense between the ages of 12-18. Conclusion: The study focuses on the impacts of socioeconomic statuses on youth crime. Accordingly, five socioeconomic statuses associated with youth crime were identified. Furthermore, this study contributes to understanding the need for youth crime prevention, the current state of youth crime, and the socioeconomic statuses associated with it.
Keywords: Youth crime; socio-economic status; criminal behavior; male prisoner